2009
DOI: 10.1038/cr.2009.20
|View full text |Cite
|
Sign up to set email alerts
|

Generation of iPS cells using defined factors linked via the self-cleaving 2A sequences in a single open reading frame

Abstract: Generation of induced pluripotent stem (iPS) cells from somatic cells has been achieved successfully by simultaneous viral transduction of defined reprogramming transcription factors (TFs). However, the process requires multiple viral vectors for gene delivery. As a result, generated iPS cells harbor numerous viral integration sites in their genomes. This can increase the probability of gene mutagenesis and genomic instability, and present significant barriers to both research and clinical application studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 19 publications
1
58
1
Order By: Relevance
“…For the quantification of transduction efficiency, we introduced GFP to MEF as above and more than 70% of cells expressed GFP. To quantify efficiency of iPS generation, total number of Nanog-positive colonies were counted and calculated as percentage of infected cell numbers, which was calculated as GFP+ cells [28].…”
Section: Generation Of 4f and 2f Ips Cellsmentioning
confidence: 99%
“…For the quantification of transduction efficiency, we introduced GFP to MEF as above and more than 70% of cells expressed GFP. To quantify efficiency of iPS generation, total number of Nanog-positive colonies were counted and calculated as percentage of infected cell numbers, which was calculated as GFP+ cells [28].…”
Section: Generation Of 4f and 2f Ips Cellsmentioning
confidence: 99%
“…More importantly, the generation of patient-specific and disease-specific (4) iPS cells has the potential to greatly impact the future of regenerative medicine, drug development, as well as our basic understanding of specific disease mechanisms. With the fast progress in this field, different reprogramming strategies have been developed, including using nonintegrating adenoviruses (5), two factors with small molecules (6), reprogramming with a polycistronic cassette containing all four factors (7,8), excisable transposons (9,10), and more recently, virus-free plasmid (11,12). However, the majority of these studies use skin fibroblasts as the parental cells, which usually requires at least 4 weeks to expand from a single skin biopsy to get enough starting cells for reprogramming.…”
mentioning
confidence: 99%
“…Indeed, Esrrb has been used as a factor to reprogram somatic cells back to a pluripotent state. In the presence of Oct4 and Sox2, Feng et al (2009) demonstrated that Esrrb could replace Klf4 as an enhancer to reprogram mouse fibroblasts into iPSC, albeit with lower reprogramming efficiency (Feng et al, 2009a). Furthermore, another family member Esrrg also possesses a similar reprogramming ability when used in conjunction with Oct4 and Sox2 (Feng et al, 2009a).…”
Section: Esrrbmentioning
confidence: 96%